The Effectiveness of Paradoxical Timetable Therapy on Rumination and Referential Thinking in Women with OCD - Namazi, Zahra; Anasseri, Mehryar (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: Obsessive thoughts are persistent, recurring thoughts, desires, or imaginations experienced intrusively and unwillingly. This study aimed to determine the effectiveness of paradoxical timetable therapy on mental rumination and referential thinking in women with obsessive-compulsive disorder. Materials and Methods: The study was quasi-experimental, utilizing a pre-test, post-test, and follow-up design with a control group. The statistical population included all women in Tehran diagnosed with obsessive-compulsive disorder in 2023. Twenty-four women were selected non-randomly and then randomly assigned to experimental (12 persons) and control (12 persons) groups. The experimental group participated in eight sessions of paradoxical timetable therapy, with 11 successfully completing the therapy, while the control group received no intervention. For equalization, the number of participants in both groups was adjusted based on the dropout rate in the experimental group. The study utilized questionnaires for mental rumination and referential thinking. Data were analyzed by analysis of variance with repeated measurements in SPSS 22. Findings: Results showed that the paradoxical timetable program significantly improved mental rumination (F = 10.89, p < 0.001) and referential thinking (F = 10.83, p < 0.001). Conclusion: Based on the findings, interventions based on this approach could effectively improve mental rumination and referential thinking in women with obsessive-compulsive disorder.